411. MAJOR INTRAOPERATIVE COMPLICATIONS IN MINIMALLY INVASIVE ESOPHAGECTOMIES. (24th September 2022) - Söderström, Henna; Moons, Johnny; Nafteux, Philippe; Uzun, Eren; Grimminger, Peter; Luyer, Misha DP; Nieuwenhuijzen, Grard AP; Nilsson, Magnus; Hayami, Masaru; Degisors, De Sebastien; Piessen, Guillaume; Vanommeslaeghe, Hanne; et al.
Abstract: Studies have shown minimally invasive esophagectomy (MIE) to be a feasible surgical technique in treating esophageal carcinoma, with equal oncological results as open surgery. The number of MIEs in Europe are increasing. Postoperative complications have been recently reviewed by a multicenter study that benchmarked MIE outcomes. There are no studies, to date, regarding major intraoperative complications during MIE and their effect on patient survival. Data was gathered retrospectively from 10 European centers with a minimum MIE experience of 3 years and more than 20 procedures annually. All intention-to-treat, minimally invasive laparoscopic/thoracoscopic esophagectomies with gastric conduit reconstruction for esophageal- and GE junction cancers operated between 2003–2019 were reviewed. Major intraoperative complications were defined as loss of conduit, erroneous transection of vascular structures, significant injury to other organs including bowel, heart, liver or lung, splenectomy, major anesthesiologic complications including intubation injuries, arrhythmias, pulmonary embolism and myocardial infarction. We also included minor intraoperative events that led to additional repair or resection of vascular structures or airways. Amongst 2862 MIE cases we identified 99 patients with 103 intraoperative complications. Of the 34 different complications the most common were vascular lesions during laparoscopy (n = 40). There were 20 splenic artery and -capsular injuries, 11 requiring splenectomy. Four losses of conduit due to gastroepiploic artery injury and five colon injuries were reported. Six tracheobronchial lesions needed repair, and 12 patients had significant lung parenchyma injuries. During thoracoscopy nine of the 13 cases with bleeding were converted and an additional 5 patients required postoperatively emergency re-intervention for thoracic bleeding. There were 2 on-table deaths. 10 of the 99 patients died in-hospital. This study offers a good overview of the wide range of possible intraoperative complications. Knowing the pitfalls can help trainees, and experienced surgeons, avoid common complications. Unfortunately, this study does not offer us incidence, which would require a prospective trial. On-table deaths are exceedingly rare. There is a possible underreporting of complications, an issue not avoided by implementing specific surveying criteria. Surgical registries need to capture intraoperative complications better in the future.